The Role of Transformational and Transactional Leadership Style of Managers on Organizational Performance of the Staff of the University of Qom - Reza Jafariharandi (Pizhūhish/hā-yi rahbarī va mudīriyyat-i āmūzishī, 2018)
Context: In the age of global competition, performance evaluation is essential for the survival of the organization. Here, the leadership style is of paramount significance, and the main reason to assess and measure organizational performance is to increase the organization overall effectiveness. Purpose: The aim of this study is to investigate the relationship betweenTransformational and Transactional Leadership Style and organizational performance of the staff of University of Qom Method: The study is applied with library–field data collection procedure and the methodology is correlational. The statistical population consists 440 staff of University of Qom. The sample size was estimated by Morgan,table to number 203 that were selected by simple random cluster sampling. Bass and Avolio’s (2000) Multi-factor Leadership (MLQ) questionnaire and Hersey and Goldsmith’s (1980) Organizational Performance (Achieve) questionnaire were used as the instruments in the study, and their reliability and validity were examined by confirmatory factor analysis and Cronbach's alpha coefficient, respectively. Result: The results showed that Transformational leadership style (r = 0.31; p < 0.05) and Transactional (r = 0.17; p < 0.05) have positive and significant relationship with the organizational performance. The results of simultaneous regression showed that about 51 percent of the leadership is able to explain and predict changes in organizational performance (r = 0.716; R2 = 0.512; Adj = 0.134) that its highest level is related to transformational leadership with beta factor of 0.36 (β = 0.36). Conclusion: It came to light that there is a meaningful relationship between leadership styles and organizational performance.